Acquired Hemophilia A in IgG4-Related Disease: Case Report, Immunopathogenic Study, and Review of the Literature - Sanges, Sébastien; Jeanpierre, Emmanuelle; Lopez, Benjamin; Russick, Jules; Delignat, Sandrine; Carpentier, Benjamin; Dubois, Romain; Dubucquoi, Sylvain; Guerrier, Thomas; Hachulla, Éric; Hatron, Pierre-Yves; Paris, Camille; et al. (Frontiers in Immunology, 2020)
We report the observation of a 75-year-old patient referred for cervical lymphadenopathies. A pre-lymphadenectomy blood work revealed an asymptomatic elevation of aPTT with low factor VIII (FVIII) levels and high anti-FVIII antibodies titers, consistent with acquired hemophilia A (AHA). Histological work-up of a cervical lymphadenopathy revealed follicular hyperplasia with IgG4+ lymphoplasmacytic infiltration; serum IgG4 levels were markedly elevated, compatible with IgG4-related disease (IgG4-RD). He was successfully treated with a 9-month course of prednisone, secondarily associated with rituximab when an AHA relapse occurred. As this patient presented with an unusual association of rare diseases, we wondered whether there was a link between the 2 conditions. Our first hypothesis was that the anti-FVIII autoantibodies could be directly produced by the proliferating IgG4+ plasma cells as a result of broken tolerance to FVIII. To test this assumption, we determined the anti-FVIII IgG subclasses in our patient and in a control group of 11 AHA patients without IgG4-RD. The FVIII inhibitor was mostly IgG4, with an anti-FVIII IgG4/IgG1 ratio of 42 at diagnosis and 268 at relapse; similar values were observed in non-IgG4-RD AHA patients. As a second hypothesis, we considered whether the anti-FVIII activity could be the result of a non-specific autoantibody production due to polyclonal IgG4+ plasma cell proliferation. To test this hypothesis, we measured the anti-FVIII IgG4/total IgG4 ratio in our patient, as well as in several control groups: 11 AHA patients without IgG4-RD, 8 IgG4-RD patients without AHA, and 11 healthy controls. We found that the median [min-max] ratio was higher in AHA-only controls (2.4 10-2 [5.7 10-4-1.79 10-1]), an oligoclonal setting in which only anti-FVIII plasma cells proliferate, than in IgG4-RD-only controls (3.0 10-5 [2.0 10-5-6.0 10-5]), a polyclonal setting in which all IgG4+ plasma cells proliferate equally. Our patient had intermediate ratio values (2.7 10-3 at diagnosis and 1.0 10-3 at relapse), which could plead for a combination of both mechanisms. Although no definitive conclusion can be drawn, we hypothesized that the anti-FVIII autoantibody production in our IgG4-RD AHA patient could be the result of both broken tolerance to FVIII and bystander polyclonal IgG4+ plasma cell proliferation.